Experiment and Simulation Study on the Dynamic Response of RC Slab under Impact Loading - Yue Wang; Jun Liu; Zhimin Xiao; Futian Zhao; Yi Cheng (Shock and Vibration)
Reinforced concrete (RC) slab is an important component in civil construction and protection engineering, and its dynamic response under impact loading is a complex mechanical problem, especially for two or multiple continuous impact loads. In this paper, a series of drop hammer impact tests were carried out to investigate the dynamic response of RC slabs with two successive impacts. The time history of impact force and the failure characteristic of the slab surface were recorded. Moreover, four influence factors, including slab thickness, reinforcement ratio, impact location, and drop hammer height have been discussed. Besides, a 3D numerical model based on the finite element method (FEM) was established to expand the research of constrained force, deflection, and vertical stress of an RC slab. The results show that increasing the slab thickness and reinforcement ratio can improve the impact resistance of an RC slab. The impact point location and drop hammer height have a great influence on the dynamic response of the RC slab. In addition, the RC slab will have more obvious damage under the second impact, but the dynamic response becomes weaker. It may be because of the local damage in the concrete caused by the first impact that would weaken the propagation of vibration.